INVESTIGATION INTO THE FORMATION AND MECHANICAL-PROPERTIES OF A BIOACTIVE MATERIAL BASED ON COLLAGEN AND CALCIUM-PHOSPHATE - Clarke, K; Graves, S; Wong, A; Triffitt, J; Francis, M; Czernuszka, J (1993)
A biomaterial composite was formed by the room-temperature precipitation of calcium phosphate (in the form of brushite) on to collagen. It was found that the addition of 1 mM O-phosphoserine (Ser P) causes the morphology of the brushite crystals to change from large plates to small needles. An increase in the surface coverage and weight fraction of brushite incorporated into the collagen was observed. The mechanical properties of this composite were tested in the wet state. The ultimate tensile strength (UTS) was 45 MPa compared with 34 MPa for the wet collagen. Osteoblastic differentiation was promoted on the surface of the material and new bone formed. © 1993 Chapman and Hall.